Analysis of the red and green optical absorption spectrum of gas phase ammonia. (April 2018) - Zobov, Nikolai F.; Coles, Phillip A; Ovsyannikov, Roman I.; Kyuberis, Aleksandra A.; Hargreaves, Robert J.; Bernath, Peter F.; Tennyson, Jonathan; Yurchenko, Sergei N.; Polyansky, Oleg L.
Highlights: Visible wavekength spectra of ammonia recorded at Kitt Peak in 1980 analysed. Analysis uses combination differences and two variational linelists. 234 and 107 lines assigned in the red and green regions respectively. Graphical abstract: Abstract: Room temperature NH3 absorption spectra recorded at the Kitt Peak National Solar Observatory in 1980 are analyzed. The spectra cover two regions in the visible: 15, 200 – 15, 700 cm − 1 and 17, 950 – 18, 250 cm − 1 . These high overtone rotation-vibration spectra are analyzed using both combination differences and variational line lists. Two variational line lists were computed using the TROVE nuclear motion program: one is based on an ab initio potential energy surface (PES) while the other used a semi-empirical PES. Ab initio dipole moment surfaces are used in both cases. 95 energy levels with J = 1 − 7 are determined from analysis of the experimental spectrum in the 5 ν NH (red) region and 46 for 6 ν NH (green) region. These levels span four vibrational bands in each of the two regions, associated with stretching overtones.